Sequence characterization of a Peruvian isolate of sweet potato chlorotic stunt virus: Further variability and a model for p22 acquisition - Cuéllar, Wilmer Jose; Cruzado, R.; Fuentes, S.; Untiveros, M.; Soto, M.; Kreuze, Jan F. (Elsevier, 2011)
Sweet potato chlorotic stunt virus (SPCSV) is probably the most important virus infecting sweetpotato worldwide, causing severe synergistic disease complexes with several co-infecting viruses. To date only one isolate (Ug), corresponding to the EA strain has been completely sequenced. It was later shown to be unusual in that, in contrast to most isolates, it encoded an additional p22 protein at the 3′ end of RNA1. We report the complete sequence and genome organization of a Peruvian isolate of SPCSV (m2-47) as determined by siRNA deep sequencing. We confirm that the ORF encoding p22 is lacking from m2-47 and all tested Peruvian and South American isolates, whereas additional isolates containing p22 were identified from Uganda. Other potentially important genomic differences such as two small ORFs encoding putative small hydrophobic proteins instead of one, upstream the hsp70h gene and a more divergent sequence at its RNA1 3′-UTR in contrast to SPCSV isolates that contain p22 are discussed and a model for recent acquisition of p22 in Uganda is proposed. A role for p22 as a pathogenicity enhancer of SPCSV is also provided by complementary expression of p22 in transgenic sweetpotato plants.